(untitled) (International Journal of Biomedical Research, 2015)
Introduction: The liquid vaporizers are very commonly used as residential insecticides in developing countries. Neurotoxic effects of pyrethroids have been reported earlier but studies regarding their histopathological effects on motor cortex area of cerebrum are rare. So the present study was planned to assess and compare the effects of pyrethroid based mosquito repellent inhalation in the motor cortex of rat CNS. Method: Twenty albino rats were divided into two groups of control and experimental. Rats in experimental group were exposed to 3.2% w/v prallethrin vapours 12 hours daily for 180 days. Control animals were kept under identical conditions without exposure to said repellent. The animals were sacrificed after 180 days. Their Cerebrum removed and processed. Sections cut and stained with Haematoxylin,Eosin and thionin . Result: Neurohistological alteration in our study in experimental rats were, loss of organisation of the cortical layer, increased density of inflammatory cells and initial signs of neuronal damage when compared to control ones Conclusion: The findings of our study establish that pyrethroids given by inhalational route do cause neurotoxicity on chronic exposure as shown by inflammatory and degenerative changes in the histological sections of CNS.